2019
DOI: 10.1002/aoc.5089
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectra, crystal structures and anticancer studies of 26‐membered macrocyclic dibutyltin(IV) dithiocarbamate complexes: Single‐source precursors for tin sulfide nanoparticles

Abstract: Four new macrocyclic dinuclear dibutyltin(IV) dithiocarbamate complexes of the type [Bu2Sn(dtc)]2, where dtc = hexane‐1,6‐diylbis(4‐fluorobenzyldithiocarbamate) anion (1), hexane‐1,6‐diylbis(4‐chlorobenzyldithiocarbamate) anion (2), hexane‐1,6‐diylbis(furfuryldithiocarbamate) anion (3) and hexane‐1,6‐diylbis(pyrrole‐2‐ylmethyldithiocarbamate) anion (4), have been prepared. The dithiocarbamate ligands efficiently self‐assemble with Bu2Sn(IV) to form bimetallic 26‐membered macrocycles. All the complexes have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…As with many of the compounds in this overview, the synthesis was facile such as in the metathetical reaction leading to 51: the diorganotin dichloride was reacted with K 2 [L 21 ]. Additional interest in 59-61 related to their putative anti-cancer potential along with utility as precursors for the deposition of tin sulphide nanomaterials [64], each being classical applications of organotin dithiocarbamates [91]. The screening for anti-cancer potential indicated that the halogen-containing substituents in the dithiocarbamate ligands, as in 59 and 60, increase the cytotoxicity [64].…”
Section: Coordination Chemistry Of Organotin Poly-dithiocarbamate Commentioning
confidence: 99%
See 4 more Smart Citations
“…As with many of the compounds in this overview, the synthesis was facile such as in the metathetical reaction leading to 51: the diorganotin dichloride was reacted with K 2 [L 21 ]. Additional interest in 59-61 related to their putative anti-cancer potential along with utility as precursors for the deposition of tin sulphide nanomaterials [64], each being classical applications of organotin dithiocarbamates [91]. The screening for anti-cancer potential indicated that the halogen-containing substituents in the dithiocarbamate ligands, as in 59 and 60, increase the cytotoxicity [64].…”
Section: Coordination Chemistry Of Organotin Poly-dithiocarbamate Commentioning
confidence: 99%
“…Additional interest in 59-61 related to their putative anti-cancer potential along with utility as precursors for the deposition of tin sulphide nanomaterials [64], each being classical applications of organotin dithiocarbamates [91]. The screening for anti-cancer potential indicated that the halogen-containing substituents in the dithiocarbamate ligands, as in 59 and 60, increase the cytotoxicity [64]. With the exception of 65, each of the di-nuclear structures in 51-66 is disposed about a centre of inversion; in 51, two independent molecules comprise the asymmetric unit, each being centrosymmetric.…”
Section: Coordination Chemistry Of Organotin Poly-dithiocarbamate Commentioning
confidence: 99%
See 3 more Smart Citations